New Composite Materials Modified with Nano-Layers of Functionalized Polymers for Bioanalysis and Medical Diagnostics - Kapustin, Dmitry; Prostyakova, Anna; Bryk, Yana; Yagudaeva, Elena; Zubov, Vitaly (IntechOpen, 2011)
None